Moving Load Analysis of Laminated Porous Micro Beams Resting on Elastic Foundation - Akbaş, şeref Doğuşcan (World Scientific, 2023)
This research highlights dynamic displacements of laminated porous micro beams resting on elastic foundation under moving load. In the constituted equation of laminated micro scaled beam, the modified coupled stress theory is used in order to determine the size effect. Each layer is considered as identical and porosity distribution and assumed as uniform. Lagrange technique is applied in achieving governing equations, and Ritz method within algebraic polynomials is used for solution. For dynamic solution steps, Newmark average acceleration method is used within time domain. Influences of porosity coefficients, length scale parameter, foundation parameter, order of laminas, fiber orientation angles on dynamically deflections of laminated micro beam are investigated. © 2023 World Scientific Publishing Europe Ltd.
Keywords: dynamic analysis; laminated composites; micro beams; moving load; Porosity; Winkler foundation